Different Surgical Strategy for Patients with Cervical Angina: A Potential Role of Luschka's Joint Osteophyte. Issue 6 (23rd August 2020) - Feng, Fan; Chen, Xiu‐yuan; Shen, Long; Li, Quan; Lao, Li‐feng; Shen, Hong‐xing
Abstract : Objective: Cervical angina is an underrecognized type of noncardiac chest pain and its mechanism of pain remains obscure. The objective of the current study was to investigate the clinical outcomes of different surgical strategies for patients with cervical angina and to analyze the potential pathogenesis of Luschka's joint osteophyte. Methods: From February 2013 to March 2018, a prospective study on cervical angina was performed in our hospital. All patients who were diagnosed with both noncardiac chest pain and cervical pathology were identified. During admission, they consulted with a cardiologist and underwent strict cardiac workups to exclude true angina pectoris. The included 41 patients were randomly divided into two groups according to different surgical strategies of whether or not to remove Luschka's joint osteophyte during anterior cervical decompression surgery: the osteophyte resection (OR group) and the nonresection (NR group). Results: The OR group consisted of 21 patients (8 men and 13 women) with a mean age of 54.7 years (range, 41–65 years). The NR group was composed of 20 patients (9 men and 11 women) with an average age of 56.3 years (range, 43–68 years). Before surgery, the mean duration of symptoms was 6.1 months (range, 4–20 months). The Luschka's joint osteophytes were located at C6 –C7 (19 cases, 46.3%), C5 –C6 (17 cases, 41.5%), and C4 –C5 (4 cases, 12.2%). Their average area was 34.85 mm 2 and the average length were 5.09 mm. No statistically significant differences in demographic characteristics were detected between the two groups ( P  > 0.05). After operation, there were significant improvements in the Japanese Orthopedic Association score and the Neck Disability Index score in both groups ( P  < 0.05). However, the visual analogue scale score for chest pain in the OR group was statistically lower than that in the NR group (1.4 ± 1.0 vs 2.1 ± 1.6, P  < 0.05). In the OR group, the results of cervical spine surgery were excellent in 18 patients (85.7%), and fair in 3 patients (14.3%). In the NR group, there were 10 patients (50.0%) with excellent results, 9 patients with fair results (45.0%), and 1 patient with poor results (5.0%). Notably, there were statistically significant differences between the two groups (χ 2 = 6.265, P = 0.044). The average follow‐up was 31 months (24–52 months). Conclusion: Anterior cervical decompression surgery with resection of Luschka's joint osteophyte can effectively reduce cervical angina symptom and improve the patient's quality of life. In addition to nerve root compression, Luschka's joint osteophyte may be another pathogenic factor in cervical angina. Abstract : Anterior cervical decompression surgery with resection of Luschka's joint osteophyte can effectively reduce cervical angina symptom and improve the patient's quality of life. In addition to nerve root compression, Luschka's joint osteophyte may be another pathogenic factor in cervical angina.